An unpublished document of the Vatican Secret Archives about the conquest: a papal brief forcing both to tear down the extramural religious buildings of Pamplona and to construct of new ones intramural - Jimeno Aranguren, Roldán (Huarte de San Juan. Geografía e Historia, 2021)
The author transcribes and analyzes a papal brief from the Vatican Secret Archives related to the conquest of Navarre. The document, written in Latin, forced to demolish the religious buildings and authorized its construction within the city. It was originally written on January 28, 1513. It was updated a few years later, at least since April 1516. Original date was crossed out and the name of King Fernando was replaced by the kings Juana and Carlos.
Keywords: Conquest of Navarre; Pamplona; Vatican Secret Archives; papal brief; Ferdinand the Catholic; Charles I; Juana I